Bacteriological analysis of air quality in the community settlement around waste disposal sites Kebon Kongok, West Lombok - Nurhidayah Nurhidayah; Mulhidin Mulhidin; Nurhidayatullah Nurhidayatullah (Jurnal Pijar Mipa, 2023)
This study aimed to determine the air quality in the community settlements around the Kebon Kongok Dusun Landfill, Suka Makmur Village, West Lombok Regency. The type of research used was an experiment using NA media as a growth medium for bacteria at 3 points passed by garbage trucks in community settlements and 1 point not passed by garbage trucks in the Kebon Kongok landfill area, Suka Makmur Village. Air quality in residential communities around the waste disposal sites (WDS) Suka Makmur Village does not meet the requirements based on the Minister of Health Regulation number 1077 of 2011 concerning the requirements for biological contaminants, namely the germ count of less than 700 CFU/m3. The air quality index is lower than the other points, namely at Point I of 3,779 CFU/m3, because Point I is a sampling location far from garbage trucks going to the TPA. The highest results in this study were obtained at Point IV, which was 6,933 CFU/m3; this was estimated because the sampling location was in a community settlement which was less than 50 meters from the Kebon Kongok TPA gate with active trucks and heavy equipment activity in the TPA. Microscopic observation obtained gram-positive bacteria at all points.